The Smicridea (Smicridea) fasciatella species group (Trichoptera: Hydropsychidae) in Brazil: six new species and new distributional records - Desiderio, Gleison Robson; Pes, Ana Maria; Andrade-Souza, Vanderly; Hamada, Neusa (European Journal of Taxonomy, 2021)
The Smicridea (Smicridea) fasciatella species group occurs from the southwestern USA, throughout Central America, the Greater Antilles islands, and most of South America, except for the Chilean subregion. It is characterized by the phallic apparatus being a simple tube with eversible internal sclerites at the apex. The fasciatella group is composed of 61 species, of which only 11 occur in Brazil, mainly in the Atlantic Forest biome in the southeastern region. In order to reduce the Linnean and Wallacean shortfalls for the Smicridea Brazilian fauna, we diagnose, describe, and illustrate males of six new species in the fasciatella group: Smicridea (Smicridea) blahniki Desiderio, Pes & Hamada sp. nov., S. (Smicridea) brevitruncata Desiderio, Pes & Hamada sp. nov., S. (Smicridea) caaguara Desiderio, Pes & Hamada sp. nov., S. (Smicridea) ipiranga Desiderio, Pes & Hamada sp. nov., S. (Smicridea) jeaneae Desiderio, Pes & Hamada sp. nov., and S. (Smicridea) polyacantha Desiderio, Pes &; Hamada sp. nov. Additionally, we provide distributional data for S. (Smicridea) albosignata Ulmer, 1907, S. (Smicridea) bivittata (Hagen, 1861), S. (Smicridea) erecta Flint, 1974, S. (Smicridea) obliqua Flint, 1974, S. (Smicridea) paranensis Flint, 1983, and S. (Smicridea) sattleri Denning & Sykora, 1968. The number of S. (Smicridea) species in Brazil increases from 21 to 27 and Smicridea is recorded from the states of Acre, Amapá, and Sergipe for the first time.